2019
DOI: 10.3390/v11070588
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Lineage of Two Traits Associated with the Coat Protein of the Tombusviridae: Silencing Suppression and HR Elicitation in Nicotiana Species

Abstract: In this paper we have characterized the lineage of two traits associated with the coat proteins (CPs) of the tombusvirids: Silencing suppression and HR elicitation in Nicotiana species. We considered that the tombusvirid CPs might collectively be considered an effector, with the CP of each CP-encoding species comprising a structural variant within the family. Thus, a phylogenetic analysis of the CP could provide insight into the evolution of a pathogen effector. The phylogeny of the CP of tombusvirids indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…RNA silencing is a well-established defence response in plantvirus infection (Gaffar & Koch, 2019). In our study, TNVA-siRNA accumulated in the inoculated leaves but did not appear to spread ( Adhab et al, 2019). In this regard, two olive mild mosaic virus (OMMV) proteins (CP and p6) were identified as suppressors of RNAi silencing (Varanda et al, 2018).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…RNA silencing is a well-established defence response in plantvirus infection (Gaffar & Koch, 2019). In our study, TNVA-siRNA accumulated in the inoculated leaves but did not appear to spread ( Adhab et al, 2019). In this regard, two olive mild mosaic virus (OMMV) proteins (CP and p6) were identified as suppressors of RNAi silencing (Varanda et al, 2018).…”
Section: Discussionmentioning
confidence: 57%
“…In our study, TNVA‐siRNA accumulated in the inoculated leaves but did not appear to spread systemically, suggesting the suppression of antiviral silencing amplification by TNVA. Recent evidence points out the possibility that tombusvirus CPs act as suppressors of RNAi silencing in Nicotiana species (Adhab et al, 2019). In this regard, two olive mild mosaic virus (OMMV) proteins (CP and p6) were identified as suppressors of RNAi silencing (Varanda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This result was not unexpected since plants elicit a reactive oxygen species (ROS) burst as an antiviral defense response, and yet RCNMV requires ROS production for efficient replication ( 56 ). It is possible that in wt RCNMV infection, viral RNA and proteins accumulate to a sufficient level to elicit a strong defense response, especially coat protein-mediated HR response ( 57 ), and the virus hijacks one of those defense responses (ROS) to accelerate viral replication. This can be seen as high levels of RNA1 accumulation in wt RCNMV infection compared to RNA1-m1 in RCNMVΔSR1f infection in which the host does not elicit a strong defense or ROS response.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a more recent study of phylogeny of the CP of tombusviruses indicated that CP representatives of the family could be divided into four clades. All tested CP members in two separate clades triggered an HR in Nicotiana section Alatae species [ 35 ]. Moreover, a previous study had shown that several members of Nicotiana section Alatae carry functional N′ orthologues [ 34 ] and implied that N′ and N′ orthologues might have been inherited from a common ancestor followed by evolution to confer tobamovirus and tombusvirus resistance to Nicotiana genus species.…”
Section: Coat Proteins (Cp)mentioning
confidence: 99%
“…Recent studies tracing HR induction lineages and silencing suppression associated with the CPs of the Tombusviridae also support the conclusion that SSR and HR elicitation involve independent motifs. Among the four clades in the phylogenetic tree of 54 CPs tombusvirids, two separate CP clades triggered an HR in Nicotiana species of section Alatae but did not have silencing suppressor activity, whereas in one clade the CP functioned as an SSR, but lost the capacity to trigger HR in Nicotiana species [ 35 ].…”
Section: Rna Silencing Suppressors (Rss)mentioning
confidence: 99%